The Effect Of Emotional Intelligence And Learning Motivation On Students' Academic Achievement At SMA PGRI 2 Depok - Lestiyadi, Ayu Puspa; Lestari, Della Ayu; Pratama, Agus Kurniawan; Firdaus, Muhammad Iqbal (Doctoral Program of Social Science, Pasundan University, 2025)
Emotional intelligence and learning motivation are important factors influencing student academic achievement. Various educational issues, such as low learning motivation and increasing academic stress, demonstrate the need to strengthen the emotional aspect of the learning process. This Community Service (PkM) activity aims to improve students' understanding of emotional intelligence and its role in supporting student academic achievement at SMA PGRI 2 Depok. The activity was implemented through material delivery, interactive discussions, and consultations focused on emotional management, learning motivation, and social skills. The results of the activity showed an increase in students' understanding of the importance of emotional intelligence, the ability to control emotions, manage academic stress, and strengthen learning motivation. Participants also learned practical strategies that can be applied in daily learning activities. This activity received a positive response from students and was deemed capable of supporting a more effective learning process. Therefore, strengthening emotional intelligence needs to be developed sustainably to support improved student academic achievement.